Addressing barriers in comprehensiveness, accessibility, reusability, interoperability and reproducibility of computational models in systems biology. Issue 4 (8th June 2022) - Niarakis, Anna; Waltemath, Dagmar; Glazier, James; Schreiber, Falk; Keating, Sarah M; Nickerson, David; Chaouiya, Claudine; Siegel, Anne; Noël, Vincent; Hermjakob, Henning; Helikar, Tomáš; Soliman, Sylvain; et al.
Abstract: Computational models are often employed in systems biology to study the dynamic behaviours of complex systems. With the rise in the number of computational models, finding ways to improve the reusability of these models and their ability to reproduce virtual experiments becomes critical. Correct and effective model annotation in community-supported and standardised formats is necessary for this improvement. Here, we present recent efforts toward a common framework for annotated, accessible, reproducible and interoperable computational models in biology, and discuss key challenges of the field.